George's marvellous medicine - Dahl, Roald (London : Puffin Books, 2007)
George decides that his grumpy, selfish old grandmother must be a witch and concocts some marvelous medicine to take care of her.
4.4
3-6.
3-6
Keywords: Grandmothers -- Fiction; Magic -- Fiction; Grandmothers -- Fiction; Magic -- Fiction